A, The "EVALUASI PROGRAM GURU PENGGERAK ( MENGGERAKKAN KOMUNITAS PRAKTISI) DI UPT SDN 13 BINAMU KABUPATEN JENEPONTO" - Zb, Eka Aprilya Putri; Habibah, Sitti; Basri, Syamsurijal (Irfani, 2026)
This study examines the Evaluation of the Driving Teacher Program (Moving the Practitioner Community) at UPT SDN 13 Binamu, Jeneponto Regency. The Driving Teacher Program is a policy from the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia that aims to form teachers who are reflective, innovative, and able to build a collaborative culture in the school environment. Program evaluation is needed to find out the extent to which the implementation is effective and in accordance with the needs of the school. This study aims to evaluate the implementation of the Driving Teacher Program using the CIPP (Context, Input, Process, Product) evaluation model. The research uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The research informants consisted of the Principal, one Driving Teacher, and one Classroom Teacher. The results of the evaluation show that in the context aspect, the program is relevant to the needs of schools and is in line with national education policies. In the input aspect, school resources have been used quite well even though there are still limitations in facilities and external resource persons. In the Process aspect, the activities of the practitioner community run in a structured and participatory manner, but face time constraints and IT capabilities. In the Product aspect, the program has a positive impact on improving teachers' professional competence and student participation. Overall, the program is considered effective in improving the quality of learning. However, it is necessary to strengthen facilities and infrastructure, continuous assistance, and adequate facility support so that the sustainability of the program can be guaranteed